PENGARUH KNOWLEDGE MANAGEMENT TERHADAP KINERJA ORGANISASI - Basuki Basuki (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2015)
The purpose of this paper is to discuss the relationship between variables knowledge management and organizational performance in hospital at South Kalimantan. The approach this discussion is to do a literature study and examine the results of previous research study results show that the knowledge management has a relationship to organization management but can not be proven empirically. Limitations of this study that this study only on the research area in hospital of South Kalimantan, would narrow the ability to generalize the findings of the research to other areas or regions wider coverage. The data presented in this study is cross-sectional which only represents the state of any given point in time. In this research, the measurement variables of knowledge management and organizational performance is measured from the internal perspective of the organization, future studies should also involve respondents from the external organization.